An assembly and interaction of upconversion and plasmonic nanoparticles on organometallic nanofibers: Enhanced multicolor upconversion, downshifting emission and the plasmonic effect - Singh P.; Shahi P.K.; Prakash R.; Bahadur Rai S. (My University, 2025)
We present novel inorganic-organic hybrid nanoparticles (HNPs) constituting inorganic NPs, NaY0.78Er0.02Yb0.2F4, and organometallic nanofiber, Tb(ASA)3Phen (TAP). X-ray diffraction, Fourier transform infrared absorption and transmission electron microscopy analyses reveal that prepared ultrafine upconversion NPs (UCNPs (5-8 nm)) are dispersed on the surface of the TAP nanofibers. We observe that the addition of TAP in UCNPs effectively limits the surface quenching to boost the upconversion (UC) intensity and enables tuning of UC emission from the green to the red region by controlling the phonon frequency around the Er3+ ion. On the other hand, TAP is an excellent source of green emission under ultraviolet exposure. Therefore prepared HNPs not only give enhanced and tunable UC but also emit a strong green color in the downshifting (DS) process. To further enhance the dual-mode emission of HNPs, silver NPs (AgNPs) are introduced. The emission intensity of UC as well as DS emission is found to be strongly modulated in the presence of AgNPs. It is found that AgNPs enhance red UC emission. The possible mechanism involved in enhanced emission intensity and color output is investigated in detail. The important optical properties of these nano-hybrid materials provide a great opportunity in the fields of biological imaging, drug delivery and energy devices. © 2017 IOP Publishing Ltd.